WHAT DO SCIENTISTS DO? - Mumbray, Tom; Tugrul, Can; Sy, Geraldine; Preston, Matt (London : Usborne, 2023)
"A fascinating insight into the many, many amazing jobs that scientists do Explore careers in science as you meet a multitude of scientists doing a huge variety of jobs in everything from astronomy to zoology. See what they do at work and marvel at their ground-breaking discoveries, then find out how YOU could become a scientist yourself"--Publisher's description
t Investigating the universe -- t Protecting our planet -- t
Includes index.
Keywords: Scientists -- Juvenile literature; Science -- Juvenile literature; Juvenile works